2019
DOI: 10.1039/c9nr01122f
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic-imaging-guided therapy of functionalized melanin nanoparticles: combination of photothermal ablation and gene therapy against laryngeal squamous cell carcinoma

Abstract: A photoacoustic imaging-guided anticancer strategy was developed based on poly-l-lysine functionalized melanin nanoparticles by integrating thermo-gene therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…According to the authors, considered, the significant inhibition of tumor growth in vivo the proposed NP represent a valuable alternative for imaging guided GT-PTT. Another possibility in GT, which was adopted by Fan et al, is the use of small and endogenous non-coding RNA, known as microRNA (miRNA) [204]. The aforementioned miRNA In a similar way, Yang et al demonstrated the activity of a melanin-poly-l-lysine (M-PLL) polymer as a siRNA vehicle, able to the overcome the endosomal barrier and to deliver into the cytoplasm the functional genetic material [202].…”
Section: Ptt-gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, considered, the significant inhibition of tumor growth in vivo the proposed NP represent a valuable alternative for imaging guided GT-PTT. Another possibility in GT, which was adopted by Fan et al, is the use of small and endogenous non-coding RNA, known as microRNA (miRNA) [204]. The aforementioned miRNA In a similar way, Yang et al demonstrated the activity of a melanin-poly-l-lysine (M-PLL) polymer as a siRNA vehicle, able to the overcome the endosomal barrier and to deliver into the cytoplasm the functional genetic material [202].…”
Section: Ptt-gene Therapymentioning
confidence: 99%
“…According to the authors, considered, the significant inhibition of tumor growth in vivo the proposed NP represent a valuable alternative for imaging guided GT-PTT. Another possibility in GT, which was adopted by Fan et al, is the use of small and endogenous non-coding RNA, known as microRNA (miRNA) [204]. The aforementioned miRNA can control cancer-associated gene expression via the regulation of the level of messenger RNA or the suppression of the target mRNA translation.…”
Section: Ptt-gene Therapymentioning
confidence: 99%
“…S20-S22). PEGylated (poly(ethylene glycol) [PEG]) melanin nanoparticles were synthesized from commercial melanin granules according to a previously reported method (16)(17)(18). The theranostic probe 1 was prepared by functionalizing melanin dots with NIR-II molecular dye 3 to form 4 dots via the traditional coupling conditions and then loading Pt(II) metallacycle 2 via π-π binding to enable both imaging and therapy ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nano-agent 1 tends to aggregate and form nanoparticles that are larger than the free melanin dots. This is due to the conjugation with the hydrophobic NIR-II dye 3 and binding with hydrophobic drugs that both decreased the hydrophilicity of the melanin dots and induced melanin dots' self-aggregation (16)(17)(18). Further experiments showed that the nano-agent 1 particle size was unchanged after incubation for 24 h in PBS containing 10% (vol/vol) FBS at 37°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation